The role of paramedics in emergency medical teams responding to natural disasters: a scoping review - Estelle C. Seton; Tom Mallinson; Carl A. Webster (Critical Care Innovations, 2025)
INTRODUCTION: Climate-related disasters have increased by over 80% in the last four decades. It is often the responsibility of Emergency Medical Teams (EMTs) to respond to the aftermath of disasters, delivering medical care and aid. Post-event evaluations have revealed flaws in the productivity and functionality of EMTs. This scoping review maps the existing literature regarding EMTs’ experiences in natural disaster response, highlighting areas of limitation in which paramedics may be able to contribute their knowledge and skills to improve the response. MATERIALS AND METHODS: A scoping review was conducted using the JBI method. The databases CINHAL, MEDLINE, Cochrane Library, and Scopus were searched with the following terms: (“paramedics” OR “paramedic” OR “emergency medical service” OR “EMT” OR “EMS”) AND (“perceptions” OR “attitudes” OR “experience” OR “disaster response”) AND (“humanitarian disaster” OR “natural disasters”) NOT (“simulation”). 340 papers were screened; 8 studies met the inclusion criteria. RESULTS: Analysis of the selected studies revealed four prominent themes: operational and access challenges, healthcare delivery and infrastructure, communication and data management, and resource utilisation and team management. CONCLUSIONS: EMT limitations range from logistical to systemic issues; there is a need to fill the public health gap currently found in EMTs. Enhancement of paramedic training on urgent and primary care around disease outbreak, and everyday healthcare provision after a disaster, would prove invaluable. Paramedics have the potential to offer a resolution to lack of basic healthcare provision after a natural disaster.